In vivo regulation of glycolysis and characterization of sugar: phosphotransferase systems in Streptococcus lactis. - Thompson, J (1978)
Two novel procedures have been used to regulate, in vivo, the formation of phosphoenolpyruvate (PEP) from glycolysis in Streptococcus lactis ML3. In the first procedure, glucose metabolism was specifically inhibited by p-chloromercuribenzoate. Autoradiographic and enzymatic analyses showed that the cells contained glucose 6-phosphate, fructose 6-phosphate, fructose-1,6-diphosphate, and triose phosphates.Dithiothreitol reversed the p-chloromercuribenzoate inhibition, and these intermediates were rapidly and quantitatively transformed into 3- and 2-phosphoglycerates plus PEP. The three intermediates were not further metabolized and constituted the intracellular PEP potential. The second procedure simply involved starvation of the organisms. The starved cells were devoid of glucose 6-phosphate, fructose 6-phosphate, fructose- 1,6-diphosphate, and triose phosphates but contained high levels of 3- and 2-phosphoglycerates and PEP (ca. 40 mM in total). The capacity to regulate PEP formation in vivo permitted the characterization of glucose and lactose phosphotransferase systems in physiologically intact cells. Evidence has been obtained for "feed forward" activation of pyruvate kinase in vivo by phosphorylated intermediates formed before the glyceraldehyde-3-phosphate dehydrogenase reaction in the glycolytic sequence. The data suggest that pyruvate kinase (an allosteric enzyme) plays a key role in the regulation of glycolysis and phosphotransferase system functions in S. lactis ML3.